Episymbiotic Saccharibacteria suppresses gingival inflammation and bone loss in mice through host bacterial modulation - Chipashvili, Otari; Utter, Daniel R.; Bedree, Joseph K.; Ma, Yansong; Schulte, Fabian; Mascarin, Gabrielle; Alayyoubi, Yasmin; Chouhan, Deepak; Hardt, Markus; Bidlack, Felicitas; Hasturk, Hatice; He, Xuesong; et al. (Cell host & microbe, 2021)
Saccharibacteria (TM7) are obligate epibionts living on the surface of their host bacteria and are strongly correlated with dysbiotic microbiomes during periodontitis and other inflammatory diseases, suggesting they are putative pathogens. However, due to the recalcitrance of TM7 cultivation, causal research to investigate their role in inflammatory diseases is lacking. Here, we isolated multiple TM7 species on their host bacteria from periodontitis patients. These TM7 species reduce inflammation and consequential bone loss by modulating host bacterial pathogenicity in a mouse ligature-induced periodontitis model. Two host bacterial functions involved in collagen binding and utilization of eukaryotic sialic acid are required for inducing bone loss and are altered by TM7 association. This TM7-mediated downregulation of host bacterial pathogenicity is shown for multiple TM7/host bacteria pairs, suggesting that, in contrast to their suspected pathogenic role, TM7 could protect mammalian hosts from inflammatory damage induced by their host bacteria. [Display omitted] •Saccharibacteria (TM7) is an epibiont that lives on the surface of Actinobacteria•Multiple TM7 isolates from periodontitis patients decrease inflammatory bone loss•TM7 reduce bone loss by modulating the pathogenicity of their host Actinobacteria•TM7 could serve a protective role for mammalian hosts in inflammatory diseases If certain bacteria are increased in disease, does that mean they are bad? Chipashvili et al. show that this may not be the case for ultrasmall Saccharibacteria. By using a mouse model for periodontitis, they determined that Saccharibacteria offer protection by reducing the pathogenicity of other bacteria in inflammatory diseases.